Diffuse and psammomatous calcification in intestinal type gastric carcinoma: Report of two cases with literature review - Nilsen YILDIRIM ERDOĞAN,; Osman Nuri HÜTEN,; Fadime BAHADIR,; Ersan SANDER, (Turkish Journal of Gastroenterology, 2019)
-